The Chemometric Approach for Verification of Paracetamol Level in Pharmacies Products Using Spectrophotometer UV-Vis - Muhammad Abdurrahman, Munir; Ahlam, Inayatullah (Academy of Sciences Malaysia, 2024)
The objective of this study is to inspect paracetamol levels in Indonesian pharmacies and whether the level of paracetamol is matched the label given. The verification of paracetamol level using a chemometric approach such as partial least squares (PLS) and principal component regression (PCR) after measured with spectrophotometer UV. The outcome of this study showed the absorbance at 242 with an R2 (0.9991) and the linear range at 1.0 – 6.0 µg·mL-1. The accuracy was satisfactory and obtained at 99.18%. The satisfactory outcomes revealed the identification method has a good potential to be used in inspecting the paracetamol level in pharmaceutical products. Furthermore, the chemometric method used as a statistical measurement showed that there was no specific distinction to the validated approach. Thus, this approach can be applied in pharmacy industries specifically for small industries to ensure the medicine's safety before being distributed to the pharmacies.